Do the effectiveness principles matter for development? Evidence from aid effectiveness data - Rachel M. Gisselquist; Patricia Justino; Andrea Vaccaro (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
The Principles of Effective Development Co-operation provide an important reference point for foreign aid and international development assistance. Although the principles-country ownership, focus on results, inclusive partnerships, and transparency and mutual accountability- are framed to support more 'effective' development cooperation, there has been insufficient systematic research on their measurement and impact. We address this gap and consider what can be learned about this relationship using the Global Partnership for Effective Development Co-operation's (GPEDC) monitoring framework. We draw on standard social science approaches to conceptualization and measurement and descriptive statistical analysis to explore the relationship between adherence to the effectiveness principles and various development outcomes. We find that, across countries, the empirical relationship between currently available GPEDC data and development outcomes is tenuous at best. Shortcomings in the data are a key reason for this lack of evidence. Some of these could be fixed straightforwardly with adjustments to the indicators and data collection approaches, but many relate to inherent challenges to measurement in this area.
Keywords: 330; effectiveness principles; development cooperation; foreign aid; Global Partnership for Effective Development Co-operation; indicators